The Influence of Humanist Da'wah in Social Transformation and Social Change in Muslim Societies - Suud Sarim Karimullah (STAI Publisistik Thawalib Jakarta, 2023)
This study aims to provide a comprehensive overview of the influence of humanist da'wah in changing and influencing the process of social transformation and social change in the Muslim community. The study method involves library research and integrated literature analysis to produce an in-depth understanding. The study's results confirmed that humanist da'wah has great potential in forming a more tolerant, humane, and sustainable Muslim society. Human values in Islam become the main foundation for positive changes in the social reality of the Muslim community. The influence of humanist da'wah is not only limited to changes in thinking, behavior, and social dynamics but also embraces human values within the framework of Islamic principles. This results in an inclusive and tolerant environment, reflected in social behavior that is responsive, caring and voluntary to social needs. Nonetheless, challenges such as resistance to change, social polarization, and disinformation remain obstacles that must be overcome. There are great opportunities to harness social inclusion, cross-sectoral cooperation, and interreligious collaboration to strengthen the message of humanist da'wah.